Pharmacist-Physician Collaboration for Diabetes Care: The Diabetes Initiative Program. (June 2013) - Farland, Michelle Zingone; Byrd, Debbie C; McFarland, M Shawn; Thomas, Jeremy; Franks, Andrea S; George, Christa M; Gross, Benjamin N; Guirguis, Alexander B; Suda, Katie J
BACKGROUND: Multiple complications can arise secondary to poor control of glucose, blood pressure, and cholesterol in a patient with diabetes. OBJECTIVE: To evaluate the effect of a pharmacist-physician collaboration on attainment of diabetes-related measures of control. METHODS: This was a prospective, multicenter, cohort study. Patients were enrolled from 7 practice sites throughout Tennessee if they had been diagnosed with type 2 diabetes, were aged 18 years or older with a life expectancy greater than 1 year, and were English speaking. Pregnant women were excluded. Patients were followed for 12 months following enrollment by informed consent. The pharmacist-physician collaboration method was established prior to study initiation. Primary outcomes included hemoglobin A1c (A1C), number of patients with A1C less than 7%, and percentage of patients with A1C greater than 9%. RESULTS: Of the 206 patients enrolled, the mean age was 59.73 years, and most were male (59.71%) and white (66.02%). The A1C was reduced by an average of 1.16% (p < 0.0001). The proportion of patients with A1C less than 7% increased from 12.75% at baseline to 36.76% at study conclusion (p = 0.0002). The proportion of patients with A1C greater than 9% decreased from 34.15% to 16.50%, (p < 0.0001). CONCLUSIONS: Pharmacist-physician collaborative management at multiple practice locations and types of setting (eg, private, academic, Veterans Affairs medical center) has a positive impact on glycemic control and diabetes-related health maintenance. This was accomplished without increasing the total number of antihyperglycemic agents prescribed and without an increase in patient-reported episodes of hypoglycemia.